Integrated Surgical, Nursing, and Rehabilitation Approaches in Ankle Arthroplasty - Alonazi, Rashed Sultan Ali; Hassan Abdallah ALkhawlani; Faiz Ali Ahmed Kaabi; Zahara Salman Hamid Almaqadi; Muteb Abdullah Al-Otaibi; Moatsem Eid Saleh ALsenani; Waleed Mohammed Hussien Tomehi; Zahra Ahmed Aysh Alsmaeil; Dalal Mohammed Rashed Aldossary; Ibrahim Abbas Ahmed ALawad; Nouf Ibrahim Ahmad Alknani (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background: <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Total ankle arthroplasty (TAA) is a motion-preserving surgical procedure for end-stage ankle arthritis, historically managed with ankle arthrodesis (fusion). While arthrodesis provides reliable pain relief, it sacrifices joint motion, leading to altered gait mechanics and secondary arthritis in adjacent joints. TAA has evolved through several generations of implant designs to better replicate native ankle biomechanics and improve long-term outcomes. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim: <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">The procedure aims to alleviate pain and restore functional ankle motion, thereby enabling patients to resume higher levels of daily activity. It seeks to provide a more physiological alternative to fusion, distributing forces more evenly across the lower extremity to prevent degenerative changes in neighbouring joints. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods: <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">TAA involves the resection of degenerated tibial and talar joint surfaces and their replacement with prosthetic components. The standard surgical approach is anterior, utilizing specialized cutting guides for precise bone preparation. Modern, third-generation implants often feature mobile-bearing designs and are supported by advanced preoperative planning, including CT scans and patient-specific instrumentation. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results: <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Successful TAA results in significant pain reduction, improved range of motion, and a more normalized gait. However, the procedure carries risks, including wound healing complications, prosthetic joint infection, intraoperative fracture (particularly of the medial malleolus), and long-term issues like component loosening and osteolysis. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion: <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">When performed on carefully selected patients by a coordinated, interprofessional team, TAA is a clinically significant intervention that effectively restores function and enhances quality of life, positioning it as a pivotal motion-preserving option in the management of end-stage ankle arthritis.